Biomimetic heterogeneous multiple ion channels: a honeycomb structure composite film generated by breath figures. Issue 24 (7th June 2016) - Han, Keyu; Heng, Liping; Wen, Liping; Jiang, Lei
Abstract : We design a novel type of artificial smart multiple nanochannel, which displays the same ionic rectification direction even when the charge polarity in the channel wall reverses. Abstract : We design a novel type of artificial multiple nanochannel system with remarkable ion rectification behavior via a facile breath figure (BF) method. Notably, even though the charge polarity in the channel wall reverses under different pH values, this nanofluidic device displays the same ionic rectification direction. Compared with traditional nanochannels, this composite multiple ion channel device can be more easily obtained and has directional ionic rectification advantages, which can be applied in many fields.